Speech Delay in Children Aged 4–5 Years as a Barrier to Early Childhood Language and Communication Development - Hendriadi, Hendriadi; Fadillah, Fitri; Ajriani, Elsa; Seha, Arma Atus (STIT Ahlussunnah Bukittinggi, 2025)
The development of language and communication is a fundamental aspect of early childhood growth, especially at the ages of 4–5 years, which are known as the golden period for language development. However, at this stage, there are still children who experience speech delays, which hinder their communication abilities and social interaction skills. This study aims to describe the condition of speech delay in children aged 4–5 years, identify the forms of speech delays experienced by the children, and analyze internal and external factors that contribute to the occurrence of speech delay. This research employs a descriptive qualitative approach with a case study method. The research subjects consist of ten children aged 4–5 years, along with teachers and parents. Data were collected through observation, interviews, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that children with speech delay demonstrate limitations in expressive and receptive language abilities, low vocabulary mastery, and difficulties in forming complete sentences. The factors causing speech delay include internal factors, such as low self-confidence and developmental language barriers, as well as external factors, including limited language stimulation within the family environment and excessive use of digital devices. This study emphasizes the importance of early detection and collaboration between educators and parents in providing appropriate language stimulation for young children.